Boiler operator's handbook - Bozzuto, Carl (River Publishers, 2021)
With the increased interest in climate impacts, sustainability, and efficiency more responsibility is being placed on boiler operators to help improve performance and reduce emissions. This 3rd edition of the Boiler Operator⁰́₉s Handbook is intended to help such operators in the quest for improved operability and performance of their boilers and their plants. The theme of this book is to "operate wisely". The goal is to instill not only "know how" but "know why". The main details have been provided by the original author, Mr. Ken Heselton. This updated version has been somewhat expanded to include a wider range of examples and some of the more recent environmental requirements. To illustrate these points, topics include multi boiler operations, understanding the plant load, maintenance issues, and controls. Every plant is different. However, it is hoped that with the information provided in this book, the wise operator will be able to address the various unique issues posed by the specific plant and provide timely solutions to meet the present-day requirements